Trait‐based diversity of deep‐sea benthic megafauna communities near the Deepwater Horizon oil spill site. (11th September 2020) - Nunnally, Clifton C.; Benfield, Mark C.; McClain, Craig R.
Abstract: Deep‐sea ecosystems are fragile yet diverse habitats that are sensitive to disturbance. In the northern Gulf of Mexico deepwater extraction of hydrocarbons led to the accidental release of four million barrels of oil from the Macondo wellhead in 2010. The release of oil combined with the addition of dispersant at depth and the resulting delivery of oiled "marine snow" led to dramatic disruptions of diversity and ecosystem services within the near field deep‐sea benthic communities. Analysis of the biological trait diversity of the surrounding megabenthos reveals notable loss of traits that may explain the stunted recovery of communities within 2 km of the wellhead. The present megafauna show complete loss of some traits relating to tier, motility, and feeding mechanisms. Functional evenness was higher than in surveyed unaffected sites, highlighting some loss of trait space, reflecting increasing abundances of scavengers and the loss of sessile invertebrates. Loss of biological traits that aid in ecosystem resilience has impeded recovery of benthic communities severely impacted by the Deepwater Horizon oil spill.